The Determinants of Stock Market Development in Nepal - Pyakurel, Indra Prasad (Journal of Vishwa Adarsha College, 2024)
This research investigates the determinants of stock market development in Nepal from 2003 to 2022 using a quantitative approach. Utilizing time series data, the study employs Pearson correlation and Ordinary Least Square (OLS) methods to analyze the relationship between macroeconomic variables, including income level, banking sector development, gross domestic savings, macroeconomic stability, private capital flows and stock market liquidity and stock market development, specifically market capitalization. The results indicate that banking sector development and private capital flows significantly influence stock market development, suggesting a crucial role for financial institutions and foreign investment in shaping and fostering the growth of Nepal's stock market. However, no significant relationship has been found between income level, gross domestic savings, macroeconomic stability, stock market liquidity, and stock market development. These findings help to design policies to stabilize or stimulate the stock market in Nepal.